PENGARUH MEKANISME CORPORATE GOVERNANCE, PROFITABILITAS DAN STRUKTUR KEPEMILIKAN TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019 – 2021 - R. Ayu Lailatus S.DN; Antoni (Jurnal Ekonomi dan Bisnis, 2023)
This research is to analyze the influence of corporate governance mechanisms, profitability and ownership structure on earnings management. The aim is to obtain evidence of the influence of independent commissioners, audit committees, profitability and institutional ownership. Quantitative descriptive research, the research population is 65 food and beverage companies on the Indonesia Stock Exchange for the period 2019 to 2021. The author took a sample, namely purposive sampling, with data obtained from 24 companies. Using SPSS 26 statistical data techniques. Based on the data results, corporate governance, profitability and ownership structure do not have a significant effect on earnings management.